Anti-Müllerian Hormone in PCOS: A Review Informing International Guidelines. (July 2019) - Teede, Helena; Misso, Marie; Tassone, Eliza C.; Dewailly, Didier; Ng, Ernest Hy; Azziz, Ricardo; Norman, Robert J.; Andersen, Marianne; Franks, Stephen; Hoeger, Kathleen; Hutchison, Samantha; Oberfield, Sharon; et al.
Abstract : Polycystic ovary syndrome (PCOS) affects 8–13% of women. The Rotterdam diagnostic criteria include polycystic ovarian morphology (PCOM) on ultrasound, but given recognized challenges, serum anti-Müllerian hormone (AMH) is proposed as an alternative. To inform international PCOS guidelines, a systematic review was completed. Key identified gaps include large international studies in well-defined populations across the lifespan, clustering of AMH with PCOS features, relationships to long-term health outcomes, and improved quality, assay standardization, and sample handling, all needed to determine cut offs. Here we identify research priorities to address these gaps and enhance AMH utility in PCOS. Once issues are addressed, AMH levels could replace more costly and less accessible ultrasound in PCOS diagnosis. Highlights: This systematic review investigates whether serum anti-Müllerian hormone (AMH) is an effective alternative for the detection of PCOM and/or diagnosis of PCOS. There is significant heterogeneity in studies conducted in adolescents and adults, with a number of limitations identified. Studies have lacked well-defined PCOS and control populations that varied across the lifespan, used inconsistent methods for defining cut offs, variably defined PCOM in comparator studies, and had methodological assay and sample handling challenges.